2018
DOI: 10.1007/s40894-018-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sexual Orientation Disparities in Disordered Eating and Weight-Related Behaviors Among Adolescents and Young Adults: Toward a Developmental Model

Abstract: Adolescence is a sensitive period for the development of disordered eating and weight-related behaviors, and sexual minorities may be particularly at risk due to heightened minority stress and challenges related to sexual identity development. This review synthesized findings from 32 articles that examined sexual orientation disparities (each with a heterosexual referent group) in four disordered eating behaviors (binging, purging, restrictive dieting, diet pill use) and four weight-related behaviors (eating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 88 publications
(212 reference statements)
8
43
0
Order By: Relevance
“…Results showed a higher prevalence of UWCB among SMM. This finding is consistent with previous studies that show that SMM adolescents are especially at risk for disordered eating behaviors and weight‐related concerns (see Miller & Luk, for a review). Descriptive statistics also showed significant disparities on indicators that are typically associated with patterns of UWCB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results showed a higher prevalence of UWCB among SMM. This finding is consistent with previous studies that show that SMM adolescents are especially at risk for disordered eating behaviors and weight‐related concerns (see Miller & Luk, for a review). Descriptive statistics also showed significant disparities on indicators that are typically associated with patterns of UWCB.…”
Section: Discussionsupporting
confidence: 92%
“…Descriptive statistics also showed significant disparities on indicators that are typically associated with patterns of UWCB. Consistent with previous research (Miller & Luk, ), we found no differences between SMM and heterosexual males on BMI and physical activity, while SMF are more likely to be obese and less likely to physically active compared to heterosexual females.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have examined the mediating role of body dissatisfaction on the association between BMI and eating pathology among sexual minority women (i.e., same‐sex attracted). Similar to Black women, studies indicate that sexual minority women have higher BMIs and report less body dissatisfaction than heterosexual women on average (Eliason et al, ; Laska et al, ; Miller & Luk, ). Recent reviews present conflicting results on the prevalence of eating pathology among sexual minority women (Calzo, Blashill, Brown, & Argenal, ; Meneguzzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 While sexual minority adolescents experience more disordered eating behaviors, empirical evidence on sexual orientation disparities in eating behaviors, physical activity, and weight-related constructs is relatively limited. 3 Moreover, despite the importance of parental and peer influences on healthy development among sexual minority adolescents, 4 these factors have not been tested as moderators of sexual orientation disparities in physical health, which is needed to inform prevention and translational research. 5 The present study examined parental and peer influences on sexual orientation disparities in eating behaviors, physical activity, and BMI in a nationally representative sample of male and female adolescents.…”
mentioning
confidence: 99%
“…6 Past studies on sexual orientation disparities in various eating behaviors have yielded mixed findings. 3 Among adolescents in the Growing Up Today Study (GUTS), sexual minority females had higher rates of fast food consumption than heterosexual females, whereas sexual minority males had lower rates of fast food consumption than heterosexual males. 7 Findings from the 2005 and 2007 Youth Risk Behavior Surveys (YRBS) indicated that male and female sexual minority adolescents consumed more fruits and vegetables relative to heterosexual peers, 8 but this finding was not replicated in a female college student sample.…”
mentioning
confidence: 99%